(untitled) (Philological Studies, 2019)
The subject of this text is the work My Scenderbej (2006) by Macedonian author Dragi Mihajlovski. The paper attempts to emphasize the successfully placed compatibility between its thematic, structural and genre features, on the one hand, and the compatibility between the specific literary text and its wider contexts (poetic, theoretical, historical, socio-cultural), on the other. Precisely these aspects make My Skenderbej an interpretative multi-contextual text, illustrative of current tendencies not just in Macedonian literature, but also in the context of the tendencies in postmodern literature, theory and historiography.